1994
DOI: 10.1128/aac.38.6.1439
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro activities of new quinolones against coryneform bacteria

Abstract: The in vitro activities of eight quinolones against 115 coryneform bacteria (20 Corynebacteriumjeikeium, 15 Corynebacterium minutissimum, 15 Corynebacterium striatum, 25 Corynebacterium urealyticum, 10 Corynebacterium xerosis, 10 Corynebacterium group ANF-1, 10 Corynebacterium group 12, and 10 Listeria monocytogenes) were determined. The MICs of ciprofloxacin, ofloxacin, and sparfloxacin for 90%o of C. jeikeium, C. urealyticum, and C. xerosis isolates tested were >16 ,ug/ml. Those of BAY Y 3118 and clinaflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“…In a previous study by our group in which we evaluated 86 strains of C. striatum isolated during the period from 1991 to 1994, MIC 50 s and MIC 90 s of 1 and 128 g/ml and 4 and 16 g/ml for gentamicin and ciprofloxacin, respectively, were obtained, values much lower than those obtained in the present study. The decreased activity of ciprofloxacin against other Corynebacterium species (C. amycolatum, C. jeikeium, C. minutissimum, C. urealyticum) may also be inferred when data obtained in the present study are compared to data from previous studies conducted by our group (10,11). For all the strains mentioned above, the MIC 50 s of ciprofloxacin have increased from 4 to Ͼ8 times, whereas the proportions of strains inhibited by ciprofloxacin at 2 g/ml have decreased from 50 to 32% (C. amycolatum), 50 to 10% (C. jeikeium), 87 to 75% (C. minutissimum), and 44 to 10% (C. urealyticum).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…In a previous study by our group in which we evaluated 86 strains of C. striatum isolated during the period from 1991 to 1994, MIC 50 s and MIC 90 s of 1 and 128 g/ml and 4 and 16 g/ml for gentamicin and ciprofloxacin, respectively, were obtained, values much lower than those obtained in the present study. The decreased activity of ciprofloxacin against other Corynebacterium species (C. amycolatum, C. jeikeium, C. minutissimum, C. urealyticum) may also be inferred when data obtained in the present study are compared to data from previous studies conducted by our group (10,11). For all the strains mentioned above, the MIC 50 s of ciprofloxacin have increased from 4 to Ͼ8 times, whereas the proportions of strains inhibited by ciprofloxacin at 2 g/ml have decreased from 50 to 32% (C. amycolatum), 50 to 10% (C. jeikeium), 87 to 75% (C. minutissimum), and 44 to 10% (C. urealyticum).…”
mentioning
confidence: 61%
“…In previous studies we have observed that new quinolones are more active than older compounds against coryneform bacteria (10,11). The objective of the study described here was to determine the in vitro activity of the new fluoroquinolone gemifloxacin in comparison with those of other compounds against different species of coryneform bacteria isolated from clinical samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent studies show an alarming rate of antibiotic resistance among Corynebacterium species and other facultative, non-spore-forming, Gram-positive bacilli. Resistance to β-lactams, clindamycin, erythromycin, azythromycin, ciprofloxacin, and gentamicin is quite frequent, with vancomycin, doxycycline, fusidic acid, and prystinamycin being the agents that are most active in vitro (15). Antimicrobial susceptibility tests may be of utility when prescribing antibiotics in cases in which any of the present organisms are involved in clinical infections.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports suggest that other species may be susceptible to commonly used antimicrobial agents, but we lack reliable clinical evidence supporting these in vitro observations. It is necessary to evaluate the activities of new antimicrobial agents against coryneform bacteria of clinical importance (3,7,(10)(11)(12)19).…”
mentioning
confidence: 99%